Grace Miriam Logan interviewed by Emily Lyle in Scottish oral tradition in Australia - Logan, Grace M. (Grace Miriam); Lyle, Emily B. (Emily Buchanan), 1932- (1977)
Folkloric recording.
Grace Logan recites: Scotland is my nation (poem) [repeated] -- The Lord is my shepard (psalm).
Recorded 17 January 1977 in Australia.
Digital master available
Timed summary available.
Keywords: Logan, Grace M. -- Interviews; Scottish Australians -- Interviews; Scots -- Australia -- Interviews; Scottish Australians -- Social life and customs; Scots -- Australia -- Social life and customs; Oral tradition -- Scotland; Scotland -- Poetry